Assessment of occupational exposure to sharp injuries among health care workers in King Abdulaziz University Hospital - S. Abdulmageed, Samia; Alabbassi, Fatmah; Alradi, Mai; Alghanaim, Nebras; Banjar, Sundos; Alnakhli, Malak (International Journal Of Community Medicine And Public Health, 2018)
Background: Sharps injuries are accidental infiltrating wounds that are typically the consequences of utilizing hazardous equipment in the usual fast-paced, and stressful health care setting. As a result, exposure to blood-borne pathogens from sharps injury poses a significant risk to health care workers. These injuries predispose the staff to dangerous infections such as hepatitis B, C and HIV. The aim of the study was to assess the occupational exposure to sharps injuries among health care workers in King Abdulaziz University Hospital in Jeddah. Methods: A cross-sectional descriptive study was conducted. Nurses, residents, dentists, and housekeepers working in the surgical ward, obstetrics and gynaecology ward, emergency department, operation room, labor and delivery room, and dental clinics at King Abdulaziz University Hospital were included. A random sample of 161 subjects was recruited in this study using a self-administered structured questionnaire. Results: Of 161 participants, 53 (32.90%) had a history of sharps injury. Among them 25 (47.16%) were nurses, both surgical and gynaecological residents had the same result of 11 (20.76%), and 6 (11.32%) of them were dentists. Most of the injuries had occurred during the use of the suture needle; 24 (45.28%) suggested that work overload was the main reason for sharps injury occurrence. Conclusions: Among health care workers, nurses were especially at risk of exposure to sharps injury. The most important risk factors for injury occurrence include long working hours, continuous rotating shifts, and work overload. Also, not all of the health care workers knew about the hospital’s reporting system.